The UK code of corporate governance: link between compliance and firm performance - Shabbir, Amama; Padgett, Carol (Cranfield University School of Management, 2008)
We investigate the relation between a detailed index of non-compliance with the UK corporate governance code, and firm performance for a panel of FTSE 350 companies from 2000 to 2003. The inverse relation between the Index and total shareholder returns (TSR) implies more compliant firms enjoy higher TSR in our sample. We also find the Index to be exogenous, implying that causality runs from the Index to performance. Our economically significant results suggest that compliance matters- not just as a box ticking exercise, but as a real change in the governance of large listed companies in the UK.
Keywords: The combined code; Corporate governance; Compliance index; Firm performance